Everlasting kiss eaudiobook Everlasting series, book 1. - Ashley, Amanda (Everlasting, 2010)
New York Times best-selling author Christine Feehan hails Amanda Ashley as a master storyteller. In this seductive paranormal romance, two young lovers risk death and heartbreak to be together. Vampire Erik Delacourt is on the hunt for a Blood Thief who destroyed one of his closest friends and is draining the blood from young vampires across the city. Into his world comes Daisy O'Donnell, a young woman Erik feels a strong need to protect. But Daisy is hardly the wilting flower she appears to be.